Experimental Study of Friction Factor During Convective Heat Transfer in Miniature Double Tube Hair-pin Heat Exchanger. (2016) - Kumar, Manish; Yadav, V.K.; Verma, Bhawna; Srivastava, K.K.
Abstract: In this research paper, we have experimentally investigated the single phase fluid flow characteristics in the inner tube of miniature size concentric double tube Hair-pin heat exchanger with constant heat flux. This work was carried out for distilled water and water-ethylene glycol mixtures (0%, 10%, 20% and 25% ethylene glycol by volume) as heat transfer cold fluid flowing inside the inner tube to carry away heat from the annulus hot fluid. The obtained Friction factor and pressure drop are compared with the existing conventional correlations. Experimentally obtained pressure drop shows good agreement with theoretical values in laminar flow.